Hubungan Tingkat Pengetahuan Dengan Kecemasan Masyarakat Dalam Menghadapi Covid-19 Di Desa Trasan Klaten - Karunia Rosa; Hermawati Hermawati (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Covid-19 is a virus that can infect the respiratory system. This virus can attack anyone, people who are at risk of contracting it are people who are in close contact with Covid-19 patients, including those who treat Covid-19 patients. A person's level of knowledge in general is one of the causes of people experiencing anxiety. Anxiety can occur when someone has less knowledge. Objective; Identifying the characteristics of the respondents, knowing the level of public knowledge, knowing the level of public anxiety, analyzing the relationship between the level of knowledge and anxiety. Methods; Quantitative with correlation approach, descriptive survey method, conducted by cross sectional. The research sample was 67 respondents. Univariate and bivariate analysis using SPSS 25 program. Results; The results of the analysis showed that there was a relationship between the level of knowledge and public anxiety in dealing with COVID-19 in Trasan Klaten Village. Conclusion; There is a relationship between the level of knowledge and public anxiety in dealing with covid-19 in Trasan Klaten Village.